Enhancing maritime ESG leadership through english communication skills - Simanjuntak Marudut Bernadtua (E3S Web of Conferences)
This study investigates the role of English communication skills in developing maritime ESG (Environmental, Social, and Governance) leadership among senior cadets at Sekolah Tinggi Ilmu PelayaranJakarta. Utilizing qualitative methods, including interviews and thematic analysis, the research focused on speaking and listening competencies crucial for professional success in the maritime industry. Findings indicate varying levels of proficiency among cadets, with strong performances in negotiation, conflict resolution, and client interaction demonstrating the practical application of communication skills. Challenges identified include technical vocabulary mastery and cross-cultural communication sensitivity, suggesting targeted training needs. Recommendations include integrating communication training into technical coursework and enhancing cultural awareness modules. This study contributes to maritime education by advocating for comprehensive skill development aligned with industry demands for sustainable leadership. By equipping cadets with effective communication strategies, maritime institutions can prepare future leaders to navigate complex ESG landscapes and promote sustainable practices globally.